Assessment of interactive acoustic deterrent devices set on trammel nets to reduce dolphin–fishery interactions in the Northern Tyrrhenian Sea - Ilaria Ceciarini; Enrica Franchi; Francesca Capanni; Guia Consales; Lorenzo Minoia; Stefania Ancora; Antonella D’Agostino; Alessandro Lucchetti; Daniel Li Veli; Letizia Marsili (Scientific Reports, 2023)
Abstract Dolphin–fishery interaction is a worldwide issue affecting dolphins through bycatch and fishers through catch or gear damages. Concerning the Mediterranean Sea, problematic interactions mainly occur between common bottlenose dolphin and small-scale fisheries. Acoustic Deterrent Devices such as pingers, are one of the most widespread measures used in attempts to face this issue. Therefore, the efficiency of interactive pingers (DiD01) in protecting the trammel nets from dolphin interactions was assessed in the Northern Tyrrhenian Sea. From March to October 2021, a total of 139 fishing trials using nets with pingers (TEST) and without pingers (CTRL), respectively n = 97 and n = 42, were carried out. Non-parametric statistic of the Catch per Unit Effort, comparing control and test nets, was not significantly different (p > 0.05) using catches weights (CPUEW) while it was significant (p < 0.01) considering the number of individuals (CPUEN). Moreover, richness and relative abundance of species resulted statistically higher in test nets (p < 0.05). This finding suggests that the absence of dolphin in the neighbourhood of fishing areas thanks to the use of pingers increases the diversity of target species. Catch damages caused by dolphins were statistically higher in nets without pinger than in nets with pinger (p < 0.05). No dolphin bycatch was recorded during fishing operations.